#saverajaampat Greenpeace.id Social Movement Campaign: Public Sentiment and Government Responses on Social Media - yuanita Setyastuti; ASTINANA YULIARTI (Jurnal Komunikasi Profesional, 2026)
#saverajaampat is a social movement campaign conducted by Greenpeace Indonesia for environmental protection, revocation of nickel mining licenses, support given to indigenous peoples, sustainable tourism in Papua and public awareness and advocacy. This research aims to analyze public sentiment and response in social media on the Social movement carried out by Greenpeaceid based on #saverajaampat. This research was conducted through a qualitative approach, with a descriptive type to describe the analysis of public sentiment and response and analyze the means used in social movements on social media. Digital data was crawled from May 25, 2025 to June 14, 2025. Data analysis techniques were carried out with qualitative descriptive analysis using the Brand24 application to analyze sentiment and public response on social media based on #saverajaampat. The results showed that the Social Movement campaignagn by greenpeace.id was able to mobilize the public to participate in digital campaigning more massively than the reach of greenpeace id. The highest negative sentiment on June 4, 2025 on Tiktok Media with 66.16% was negative sentiment. The government's response was to close the licenses of four nickel mines around Raja ampat.